Assessment of right ventricular involvement in patients with anti-MDA5 Ab+ DM: a prospectively observational study with cardiac magnetic resonance imaging - Zhang, Ling; Wang, Yuli; Dai, Jinzhu; Pu, Xiaoqi; Liu, Anqi; Ni, Yifei; Wang, Jianping; Du, Jie; Ren, Yanhong; Shu, Xiaoming; Liu, Min (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAnti-melanoma differentiation-associated gene 5 dermatomyositis (anti-MDA5 Ab+ DM) is characterized by amyopathic DM with interstitial lung disease. Its impact on the right ventricle remains unclear. We aim to evaluate RV involvement in anti-MDA5 Ab+ DM patients using cardiovascular magnetic resonance (CMR).MethodsThis single-center, prospective cohort study included 43 anti-MDA5 Ab+ DM patients (24 males, mean age = 44.7 ± 11.1 years) and 30 age- and gender-matched healthy controls (18 males, mean age = 44.8 ± 10.4 years). All patients underwent CMR before treatment. RV functional parameters, including ejection fraction (RVEF), end-diastolic/end-systolic remodeling index (RVEDRI/RVESRI), and right ventricular long-axis strain (RV-LAS), and RV and LV T1 and T2 mapping were analyzed. Differences between the two groups were evaluated, and correlations with clinical data were explored.ResultsAnti-MDA5 Ab+ DM patients exhibited a significant decrease in RVEF (45.7 ± 5.9% vs. 52.7 ± 6.6%, P < 0.001) and RV-LAS across all techniques. Increased RVESRI (1.38 ± 0.14 vs. 1.29 ± 0.14, P = 0.031) indicated RV subclinical dysfunction. The RV and LV blood pool T2 ratio was elevated in patients (0.96 ± 0.02 vs. 0.94 ± 0.03, P = 0.007). Patients in the inflammatory marker-positive group exhibited significantly worse RV-LAS compared with the negative group. RV-LASIns/mid negatively correlated with hsTnl levels (r = −0.34, P = 0.026), and ferritin (FER) is moderately positively correlated with RV-LASLVapex/peri (r = 0.487, P < 0.001).ConclusionRV subclinical dysfunction is common in patients with anti-MDA5 Ab+ DM. RV parameters on CMR such as RV-LAS and RVESRI serve as valuable imaging markers for early detection and risk stratification. These findings underscore the importance of routine cardiac evaluation in anti-MDA5 Ab+ DM.